Cryptocurrency ownership and corporate risk: Empirical evidence from U.S. firms on liquidity, financial conditions, and volatility - Lukito, Richard; Soepriyanto, Gatot (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of cryptocurrency ownership on corporate volatility, focusing on external financial conditions, internal financial conditions, and liquidity crises. The research utilizes secondary data from publicly traded companies in the United States listed in the Refinitiv database for the period 2018-2023. To enhance the validity of the results, a matching procedure was implemented, in which each cryptocurrency-owning company was paired with a similar non-cryptocurrency-owning company to create a balanced control group. The analysis employed panel data regression on 384 publicly traded companies in the U.S. The findings indicate that the ratio of cryptocurrency ownership has a significant positive effect on corporate volatility. Additionally, liquidity levels also have a significant positive impact on the volatility of companies holding cryptocurrencies, suggesting that liquidity crises amplify the effect of cryptocurrency ownership fluctuations on corporate volatility. Internal financial conditions, measured by Return on Assets (ROA), exhibit a significant negative effect on the volatility of companies holding cryptocurrencies, implying that strong internal financial health mitigates the impact of cryptocurrency ownership fluctuations on volatility. Conversely, external factors such as company Beta do not influence increased volatility, which contrasts with the expectation that external factors would amplify the effect of cryptocurrency ownership fluctuations on corporate volatility. This study offers important implications for financial managers and regulators in designing risk mitigation strategies against digital asset price fluctuations.